2019
DOI: 10.1111/spc3.12498
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating a healthy neuro‐immune network: A health psychology approach

Abstract: The field of psychoneuroimmunology (PNI) examines interactions among psychological and behavioral states, the brain, and the immune system. Research in PNI has elegantly documented effects of stress at multiple levels of the neuro‐immune network, with profound implications for both physical and mental health. In this review, we consider how the neuro‐immune network might be influenced by “positive” psychological and behavioral states, focusing on positive affect, eudaimonic well‐being, physical activity, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 128 publications
(138 reference statements)
0
17
0
Order By: Relevance
“…It has been shown that MS increased the expression of IL-1 β and TNF- α genes in the hippocampus [ 35 ]. Studies have showed that some agents effectively mitigating depressive-like behaviors significantly reduced the expression of genes relevant to neuroimmune response in the hippocampus [ 36 , 37 ]. Studies have shown that limonene reduced the inflammatory response and decreased the levels of inflammatory cytokines [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MS increased the expression of IL-1 β and TNF- α genes in the hippocampus [ 35 ]. Studies have showed that some agents effectively mitigating depressive-like behaviors significantly reduced the expression of genes relevant to neuroimmune response in the hippocampus [ 36 , 37 ]. Studies have shown that limonene reduced the inflammatory response and decreased the levels of inflammatory cytokines [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although research in PNI has primarily focused on stress and other negative psychological states, there is growing recognition that positive psychological states may also modulate the immune system and neuro-immune interactions ( Bower, Kuhlman, Haydon, Boyle, & Radin, 2019 ). Here, we consider how positive psychological states, including positive affect, eudaimonic well-being, and social connection/support, are linked with antiviral immunity and inflammation.…”
Section: Positive Psychological States and Immunitymentioning
confidence: 99%
“…For example, dispositional PA predicted a stronger antibody response to hepatitis B vaccination, lower risk of developing an upper respiratory infection following infection a cold or influenza virus, and lower risk of AIDS-related mortality ( Cohen, Alper, Doyle, Treanor, & Turner, 2006 ; Marsland, Cohen, Rabin, & Manuck, 2006 ; Moskowitz, 2003 ). PA is also associated with lower levels of circulating inflammatory markers, lower production of proinflammatory cytokines by immune cells (a measure of inflammatory potential), and reduced inflammatory activity in the laboratory and in daily life ( Bower et al, 2019 ). Importantly, associations between PA and immunity are maintained in analyses controlling for negative affect, demonstrating that PA has a unique link with the immune system.…”
Section: Positive Psychological States and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The typical wireless BAN consists of three parts: medical sensor nodes (the nodes or devices are generally placed on the human body), sink nodes, and network management nodes [6]. BAN is generally constructed with a distributed strategy.…”
Section: Introductionmentioning
confidence: 99%